Analysis of building defect - Tahir Majid Complex - Faculty Of Architecture, Planning And Surveying Mara University Of Technology (UiTM) Shah Alam, Selangor Darul Ehsan / Rohaizana Ramli - Ramli, Rohaizana (2002)
Building is one of human need. And it is the most important to keep and care human from others harmful. Each building needs a requirement to fulfill a function. When the building faced the damage it would become deteriorate when not repair and remedies it. One solution to keep the building is always in good condition and good environment is must make sure it always maintain for every time and compulsory to follow the maintenance schedule planning. Building defect is divided into two categories- physical and biological defects. It was divided based on sources of the defect, if the sources is come from the physical factors so it named physical defect meanwhile if caused by biological agent it was named biological defect. Defect always will relate to effect from the building defect toward sedentary person. List of effect from the building defect are sickness, safety and cost. Meanwhile toward a building are environment/ humidity and appearance.